IMPLEMENTASI LITERASI DIGITAL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SEKOLAH DASAR - Haifa Anjani, Karin; Anggraeni Siwi , Dwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of digital literacy in Pancasila Education learning for fifth grade elementary school students and identify the obstacles faced in implementing digital literacy during Pancasila Education learning for fifth grade elementary school students. This study uses a qualitative research method with a descriptive qualitative research type. Data collection techniques were carried out using observation, interviews, and documentation. The data analysis technique for this study used interactive data analysis techniques. The results of the study indicate that the implementation of digital literacy in Pancasila Education learning on the topic "My Indonesian Cultural Diversity" in fifth grade elementary school students at Puhgogor 01 has run well through the planning, implementation, and evaluation stages of learning. In the planning stage, teachers have developed teaching modules that integrate digital media. In the implementation stage, students showed good development in digital literacy skills. Furthermore, in the evaluation stage, teachers used online quizzes with pictures to determine the level of students' understanding of the material that had been learned. There were no major obstacles. The availability of digital facilities such as chromebooks and a stable internet connection were the main factors that supported the smooth learning process. The obstacles that emerged were only minor and could be overcome by teachers through preparedness and providing alternative solutions.